Kebijakan Pelaksanaan Paten Pemerintah Untuk Produk Obat Dan Vaksin: Diskursus Sistem Pelindungan Kekayaan Intelektual Dalam Perdagangan Internasional - Margono, Suyud (Jurnal Hukum & Pembangunan, 2022)
Intellectual Property Protection system has contradiction with the Government's use of Patent Implementation Policy for Pharmaceutical Products, Medicines and Vaccines occurs in addition to the increasing need for Medicines and vaccines in the Covid-19 pandemic situation, due to the provisions of the Trade Related Aspect of Intellectual Property Rights (TRIPs) Agreement in International trade has become a legal instrument that makes intellectual property exclusively. Identification of this research problem among others: What should be the Exploitation and Protection Policies for Inventions of Vaccine Patent Products so that there are no contradictions in the Intellectual Property Rights (IPR) System for International trade? The research method is adjusted to the research topic, especially for the Intellectual Property Rights (IPR) protection system for Invention of Medicines and Vaccine product within the scope of international trade. Research finding that the Intellectual Property System does not only guarantee protection for inventions but includes efforts to adequately exploit patented drug and vaccine inventions, so that state intervention is needed not only during the Covid-19 pandemic but also for sustainability and conditions of community needs or public interest. Indonesia continues to fight for equal access to pharmaceutical drugs and vaccines for all countries. International Cooperation (both bilateral and multilateral) within the scope of international relations is aimed in strengthening cooperation to solve common problems.